Targeted Debt Relief and the Origins of Financial Distress: Experimental Evidence from Distressed Credit Card Borrowers - Dobbie, Will; Song, Jae (American Economic Review, 2020)
We study the drivers of financial distress using a large-scale field experiment that offered randomly selected borrowers a combination of (i) immediate payment reductions to target short-run liquidity write-downs to target long-run debt constraints. We identify the separate effects of the payment reductions and interest write-downs using both the experiment and cross-sectional variation in treatment intensity. We find that the interest write-downs significantly improved both financial and labor market outcomes, despite not taking effect for three to five years. In sharp contrast, there were no positive effects of the more immediate payment reductions. These results run counter to the widespread view that financial distress is largely the result of short-run constraints. (JEL G56, K35)